The influence of project teaching on creativity and achievements of students in studying social contents within the subject Nature and society - Janković, Aleksandar P.; Davidović, Andrijana Lj.; Lambić, Dragan M. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2020)
Creativity represents the point in which all contradictions of contemporary social development are summed up, refracted and reflected. Therefore, the question arises: "Is school a place that does (not) encourage creativity?" Creativity, as a psychological, social and pedagogical phenomenon, has a markedly positive impact on the overall development of a child or, in case of school, a student. The project teaching method calls for the school to be open and to be more closely connected with its environment, in order to enhance the students’ independence and creativity, self-initiative, responsibility, cooperativeness, ability to apply information and communication technologies as well as digital teaching tools as sources of knowledge. This article presents the project method as an element of stimulating students’ creativity in teaching the subject Nature and Society, planned for the third grade of elementary school. By reviewing the relevant literature as well as by experimental research on a convenience sample of students, we have identified acceptable options and some effects of applying this method. At the same time, we have also raised a number of issues that should be addressed later in order to further stimulate the development of creativity through teaching.